Optimizing irrigation and nitrogen rate can enhance the grain yield in both main and ratoon rice crop - Zhang, Qiang; Han, Yu; Qi, Mengying; Jing, Haoran; Nie, Xuanli; Yu, Guilong; Li, Zhi; Wei, Pengfei; Zhao, Haiying; Li, Mengjie; Li, Hao; Zhu, Tao (Frontiers in Plant Science, 2025)
Ratoon rice enhances yield per unit area through efficient resource use, but the interactive effects of irrigation regime and nitrogen (N) rate on its productivity remain unclear. A two-year field experiment was conducted to assess the effects of two irrigation regimes—conventional flooding irrigation (CF) and alternate wetting and moderate soil drying irrigation (WMD)—combined with five N application rates on yield, agronomic productivity, root oxidation activity (ROA), soil chemical properties, and N use efficiency (NUE) in the rice cultivar Liangyou 6326. The results showed that compared with CF, WMD increased spikelets number per panicle, total spikelet number, and filled grain rate in both main and ratoon crop, thereby enhancing the yields by 11.0% and 16.1%, respectively. These improvements were linked to elevated soil N, phosphorus, potassium content, and cation exchange capacity under WMD, which enhanced photosynthesis, ROA and dry matter production. While the interaction between N rates and irrigation regimes on yield were nonsignificant, CF exhibited declining photosynthetic capacity, yield, and NUE with reduced N. Conversely, WMD showed initial increases followed by declines, peaking at 427.5 kg N/ha (243 kg ha-1 main crop; 184.5 kg ha-1 ratoon crop). This study provides actionable strategies for sustainable ratoon rice systems by balancing water and N inputs.